Mosquito Behavior and Vertebrate Microbiota Interaction: Implications for Pathogen Transmission - Ruiz-López, María José (Frontiers in Microbiology, 2020)
The microbiota is increasingly recognized for its ability to influence host health and individual fitness through multiple pathways, such as nutrient synthesis, immune system development, and even behavioral processes. Most of these studies though focus on the direct effects microbiota has on its host, but they do not consider possible interactions with other individuals. However, host microbiota can change not only host behavior but also the behavior of other individuals or species toward the host. For example, microbes can have an effect on animal chemistry, influencing animal behaviors mediated by chemical communication, such as mosquito attraction. We know that host skin microbes play a major role in odor production and thus can affect the behavior of mosquitoes leading to differences in attraction to their hosts. Ultimately, the vector feeding preference of mosquitoes conditions the risk of vertebrates of coming into contact with a vector-borne pathogen, affecting its transmission, and thus epidemiology of vector-borne diseases. In this mini review, I provide an overview of the current status of research on the interaction between mosquito behavior and host skin microbiota, both in humans and other vertebrates. I consider as well the factors that influence vertebrate skin microbiota composition, such as sex, genetic makeup, and infection status, and discuss the implications for pathogen transmission.